Insights into the mechanical properties of a silicone oil gel with a ‘latent’ gelator, 1-octadecylamine, and CO2 as an ‘activator’ - Emiliano Carretti; Mathew George; Richard G. Weiss (Beilstein Journal of Organic Chemistry, 2010)
A detailed study of the rheological properties of silicone oil gels, made from a low-molecular-mass organic gelator, a combination of 1-octadecylamine (a latent gelator) and carbon dioxide (an ‘activating’ molecule), is reported. Information gleaned from the mechanical measurements is used to characterize the gel networks and how they respond to temperature and strain. It is shown, for example, that very precise measurements of the gel-to-sol transitions can be obtained from plots of viscosity versus temperature.